EFEKTIVITAS KOMUNIKASI PENYULUHAN PERTANIAN DALAM PEMBENTUKAN PETANI MANDIRI DI TINGKAT KELOMPOK TANI - Petrus Christologus; Mustafa Abdurrahman; Serman Nikolaus (Undana Press, 2022)
This study aims to determine the types of media, methods, materials and to determine the level of effectiveness of agricultural extension communications in the formation of independent farmers at the farmer group level of Usaha Baru in Pukdale Village, East Kupang District, Kupang Regency. The research method used is a survey method. The data used consists of primary data and secondary data. The respondent was determined by using saturated sampling technique or census in which 20 members of the New Usaha Farmer Group were sampled. The data analysis used was descriptive qualitative and Rank Sperman analysis. The results showed that the communication media of agricultural extension in the formation of independent farmers at the farmer group level Effective new businesses were interpersonal media, effective extension communication methods, namely the individual approach method and group approach, effective extension materials, namely all materials on increasing agricultural production and effectiveness. Agricultural extension communication in the formation of independent farmers at the farmer group level of the New Business is in the effective category with a score of 3.96 and a maximum score of 79.25%.